THE SOCIAL RELEVANCE OF SOCIOLINGUISTICA - Camacho, Roberto Gomes [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2016)
Focusing on data extracted from Iboruna, a corpus collected in the Northwestern region of Sao Paulo State, this paper aims at showing the social relevance of the sociolinguistic theory based on a study of variable plural marking in non-verbal predicates of a single word (nouns, adjectives and past participles). As the reiteration of marks, this variable phenomenon is largely motivated by formal parallelism, defined as an internal constraint, but it can also be especially accounted for by years of schooling, defined as an external constraint. This result, sharply social in nature, meets the main principles of Sociolinguistics postulated at its emergence fifty years ago, when Labov's thesis, The Social Stratification of English in New York City, was published.
Keywords: nominal agreement; non-verbal predicate; years of schooling; formal parallelism